Organizational Climate And Organizational Citizenship Behavior On Public Sector Organizations - Wirawan, I Komang Pasek Guna; Suardhika, I Nengah; Agung, Anak Agung Putu (The journal of contemporary issues in business and government, 2021)
Every organization certainly expects success. To achieve this success, organizations need quality human resources. The Regional Development Planning Agency (BAPPEDA) of Bali Province is one of the instruments in the government structure that has a strategic role in planning regional development. Human workers or employees are the main implementers for the success of a business. The purpose of this study was to examine and confirm the relationship between the variables of organizational climate, organizational commitment, Organizational Citizenship Behavior (OCB) and employee performance, at BAPPEDA Bali Province. Respondents in this study were all PNS employees at BAPPEDA Bali Province. The number of respondents in this study was determined to be 72 respondents using a sampling technique called non probability or often called total sampling. This study uses Structural Equation Modeling (SEM) analysis with the help of the SmartPLS program. The results of this study indicate that: 1) organizational climate has a positive and significant effect on organizational commitment, 2) organizational climate has a negative and insignificant effect on employee performance, 3) organizational climate has a positive and significant effect on organizational citizenship behavior (OCB), 4) commitment organization has a positive and significant effect on employee performance, 5) organizational commitment has a positive and significant effect on OCB, 6) OCB has a positive and significant effect on employee performance.